Health Care Challenges in Iran - M Davari; A Haycox; T Walley (Tehran University of Medical Sciences, 2005)
All health systems across the world have faced new challenges, which is primarily referable to increasing the cost of health care services as well as growing demands for new and expensive health technologies. The aim of this study is to analyse the main challenges facing the Iranian health system. A review of available governmental and relevant publications about Iranian health care system was undertaken to assess the direction of future healthcare policy. Electronic news agencies, newspapers, and parliament's electronic news also reviewed to realise policy-makers points of view about the health system. Healthcare services in Iran have had a great success in primary healthcare services in last 25 years, which is mainly attributable to National Health Networks policy. Between 1979 and 2003, average life expectancy at birth increased from 57 to 70 and infant mortality rate fell from 104 to 26 per thousand live births. Active vaccination system, very good distribution and coverage, free end point services, family planning, maternal teaching, and primary referral system are of strong advantages of health networks in Iran. However, the healthcare system is now subject to a range of new pressures that must be addressed. Many of these pressures are common to all health services (rising consumer demands and expectations for expensive new technologies, changing disease patterns, and resources shortage), but some are largely specific to Iran. Financial fairness contribution of the population to health system, responsiveness of health system, overusing new technologies, inadequate integration of health services, and inequitable distribution of the resources are of the main challenges of health system in Iran. In addition, considering demographic changes of the Iranian population in recent decades, which made Iranian population young, potential pressures due to an aging population will reveal in coming years. Many of these pressures relate to policies and the management of the system. Therefore, the role of macro planning in health and health policy is considerable to manage the pressures. Realistic targeting, well planning, and well organising could make the current system more cost-effective, equitable, and accessible to all of the population. Health Technology Assessment, as an aid in decision-making, could be a valuable part of decision-making process in Iran in improving effectiveness and efficacy of the health system.